“Proyecto de Factibilidad para la Creación de una Empresa que Ofrezca el Servicio Exequial de Cremación, Ubicada en el Sector de San Buenaventura, Ciudad de Latacunga en 2021” - Solís Karolys, Marco Efraín (2021)
This degree work was developed in adherence to the line of research: Quality management and economics for social development of the Master's program in Business Administration, of the Technical University of Cotopaxi, fulfilling the object of study of the program in , the professional ability to create, direct and manage enterprises that contribute to the business sector, in a strategic manner, attached to local, regional and national development and social responsibility. This research aims to analyze the feasibility for the implementation of a company that offers cremation funeral services in the city of Latacunga, in the year 2021. The methodology was quantitative, descriptive and experimental for the province of Cotopaxi. The stated objectives were to design a feasibility project, which was based theoretically and epistemologically on research and work previously carried out, referring to the incineration or cremation of human remains, the factors of perception and social acceptance, as others typical of the investigation. of the market, as well as the technical and financial study, which allowed concluding that, in the country, there was evidence of an existing growing demand for the cremation service, as a result of the adoption of new methods in the final disposal of dead bodies. , as well as a lack of space in cemeteries and pantheons, determining the cremation funeral service as an option to mitigate the existing problem. Ecuadorian regulations contemplate crematoria in an updated manner, thus guaranteeing the use and treatment of adequate and efficient technologies, consistent with environmental care and friendly management with the areas of influence where it was located. The investment was recovered in a period just over three years of life of the project, demonstrating a favorable level in determining its viability and feasibility.